2014
DOI: 10.1371/journal.pone.0098897
|View full text |Cite
|
Sign up to set email alerts
|

Artemisia scoparia Enhances Adipocyte Development and Endocrine Function In Vitro and Enhances Insulin Action In Vivo

Abstract: BackgroundFailure of adipocytes to expand during periods of energy excess can result in undesirable metabolic consequences such as ectopic fat accumulation and insulin resistance. Blinded screening studies have indicated that Artemisia scoparia (SCO) extracts can enhance adipocyte differentiation and lipid accumulation in cultured adipocytes. The present study tested the hypothesis that SCO treatment modulates fat cell development and function in vitro and insulin sensitivity in adipose tissue in vivo.Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 25 publications
(62 citation statements)
references
References 48 publications
4
58
0
Order By: Relevance
“…Adipogenesis Assay-Murine 3T3-L1 preadipocytes were plated and grown to 2 days postconfluence in DMEM contain- (29). Cell monolayers were aspirated and rinsed with PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Adipogenesis Assay-Murine 3T3-L1 preadipocytes were plated and grown to 2 days postconfluence in DMEM contain- (29). Cell monolayers were aspirated and rinsed with PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Murine 3T3-L1 preadipocytes were grown and differentiated as previously described [24]. Mature adipocytes were > 99% differentiated.…”
Section: In Vitro Lipolysis Assaymentioning
confidence: 99%
“…Investigation revealed that Artemisia extracts had shown hepatoprotective and hypolipidemic properties and antioxidative activity in hepatoma cells in Dgalactose-induced oxidative stress in mouse model [12][13][14]. Literature indicate that Artemisia contain an active compound which affects on skeletal cell membrane and increases insulin sensitivity and can increase adipocyte differentiation in cultured adipocytes [15][16][17]. Based on aboveCopyright © 2017, Zahedan University of Medical Sciences.…”
Section: Introductionmentioning
confidence: 95%